The end of "Made in Hong Kong"? De-industrialisation and industrial promotion policy in Hong Kong - W. Breitung (Geographica Helvetica)
This article explores spatial aspects of Hong Kong's deindustrialisation, related both to the development of closer cross-border ties and to Hong Kong's evolution as a global city. Industrial promotion has always had its place in the generally non-interventionist economic policy ofthe government. However, under the new political and economical conditions industrial promotion has moved up on the agenda. In particular, the promotion of high-tech industries is given special governmental attention. The author wams that the plans for re-industrialising Hong Kong may be based on an obsolete view of the city: the city as an isolated entity rather than as the cross-border economic agglomeration that it is growing into. The aim should be to develop a strong and productive industrial base with intra-regional co-operation for the whole agglomeration instead of just for Hong Kong.